A Hardware-in-the-Loop Facility for Integrated Vehicle Dynamics Control System Design and Validation - Soltani, Amirmasoud; Assadian, Francis (Elsevier, 2016)
Due to the increased number and the complexity of the embedded systems in today’s vehicle, there is ever increasing pressure to reduce the development cost and time to market of such systems. In recent years, Model based Development (MBD) is becoming a main stream in the development of automotive embedded systems, and Hardware-in-the-Loop (HiL) testing is one of the key steps toward the implementation of MBD approach. This paper presents the recent HiL facility that has been developed at Cranfield University. The HiL setup includes real steering and brake smart actuator, high fidelity validated vehicle model, complete rapid control prototyping tool chain, and driver-in-the-loop capability. The applications of HiL setup are including but not limited to: smart actuators system identification; rapid control development and early validation of standalone and/or integrated vehicle dynamics control systems. Furthermore, the facility can be employed for investigation on driver-vehicle interaction at the presence of standalone active steering and/or brake systems as well as various Advanced Driver Assist Systems (ADAS), such as lane keeping or adaptive cruise control systems. The capability of the HiL facility for validation of a several newly developed vehicle dynamics control systems is presented
Keywords: Automotive Control; Integrated Vehicle Dynamics Control Systems; Rapid Control Prototyping; Control Validation; Model Based Development; Hardware in the Loop (HiL); Active Steering Control; Active Brake Control